GAMIFICATION IN HYBRID MATHEMATICS TEACHING: POSSIBLE IMPACTS ON LEARNING AND ACADEMIC PERFORMANCE (Editora Impacto Científico, 2025)
The guiding question of this research is: How can the use of gamification positively impact the learning of elementary school students in hybrid Mathematics classes? This study explores the possible impact of gamification on academic performance and student learning, considering its application in a teaching model that combines face-to-face and virtual activities. Based on bibliographic research, the investigation reveals that integrating game elements—such as challenges, rewards, and point systems—into hybrid learning enhances motivation, content retention, and the development of essential skills such as problem-solving, logical thinking, and collaboration. To support this analysis, studies by authors such as Prensky (2001), Kapp (2012), and Buckley & Doyle (2017) were consulted, which examine the impact of gamification in relation to learning styles and personality traits. These perspectives enrich the understanding of how different student profiles respond to such approaches. However, its implementation requires strategic planning, adequate teacher training, and alignment with pedagogical objectives, while also addressing challenges such as unequal access to technology and adaptation to specific educational contexts. Thus, the results of this study indicate that, when applied in a structured manner, gamification in hybrid learning transforms the learning experience by integrating digital and in-person practices to enhance students' academic performance. It is concluded that this approach not only contributes to a deeper understanding of mathematical concepts but also prepares students for the challenges of the 21st century, reinforcing the role of active methodologies in contemporary education.